Studi Kasus Pelaksanaan K3 (Kesehatan dan Keselamatan Kerja) di Kawasan PT Gunbuster Nickel Industry - Ziana Walidah; Nur Arifudin; Desi Wilda Rizki Amelia; Sur Fadila (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This case study investigates the implementation of Occupational Health and Safety (K3) in the PT Gunbuster Nickel Industry area. Through in-depth analysis of policies, practices, challenges, strategies and impacts of K3 implementation, this research aims to provide comprehensive insight into the company's efforts to ensure a safe and healthy work environment for its workers. The research results show that PT Gunbuster Nickel Industry has adopted various comprehensive K3 policies and practices, including routine K3 training, work environment monitoring, and safety campaigns. However, several challenges such as employee resistance and complex working conditions remain obstacles in implementing K3. To overcome these challenges, the company has implemented proactive strategies, including increasing K3 communication and awareness, regular evaluation of working environment conditions, and active involvement of employees in efforts to prevent work-related accidents and diseases. The impact of implementing effective K3 policies at PT Gunbuster Nickel Industry includes reducing the number of work accidents, increasing productivity, and improving the company's image. This research makes an important contribution to the understanding of best practices in K3 management in the industrial sector, as well as becoming a reference for other companies in their efforts to create a safe and healthy work environment.